Effect of No-Primers Orthodontic Adhesives on the Sheer Bond Strength of Meta Molar tubes Bonded to Porcelain: An In Vitro Study/Saeid Rahmani. - Rahmani, Saeid; Llavore, Lotus D.
General objective: The purpose of this in vitro study was to determine the shear bond strength of the universal orthodontic adhesive and the two no-primers orthodontic adhesives using the metal molar tubes bonded to porcelain surfaces conditioned with HFA surface preparation.
Materials and method: Three orthodontic adhesives in three groups used to bond forty-eight (48) mandibular right first molar convertible 0.22" in. slot molar tubes (Victory Series™ 3M Unitek, Montrovia, CA to lithium discilate porcelain disks measured 7mm. X 7mm. X 3mm., conditioned with 4% HFA (Reliance Orthodontic Product, Inc., Itasca, IL) surface preparation, Group 1 the light cure conventional orthodontic composite (Transbond™ XT; 3M Unitek), Group 2 the no-primers ligh- curing system (Orthocem; FGM. DENTSCARE LTDA) and Group 3 the no-primers orthodontic composite (Heliost; Ivoclar Vivadent, Schaan Liechtenstein) used to cement the metal molar tubes on the surface of the porcelain disks (e.max; Ivolar Vivadent, Schaan Liechtenstein). The shear force applied to samples with the universal testing machine at the crosshead speed of 1 mm./min. Shear bond strength (SBS) were measured in megapascals. Statistical analysis was conducted by analysis of variance (ANNOVA). Tukey’s test and the one sample t-test to compare the mean values between and among the groups. Stereomicroscope was used to measure the amount of adhesive remaining on the porcelain after debonding the Adhesive Remnant index.
Result: There was a significant difference between the mean shear bond strength among the groups. The highest shear bond strength belonged to Group 1, which used the light cure conventional orthodontic cement (Transbond™ XT; 3M Unitek) with the mean shear bond strength of 15.40 Mpa. Group 2, non-primers light-curing system (Orthocern; FGM) cement showed 6.35 Mpa which exhibited the lowest shear bond strength among all the three groups. In Group 3 which used the no-primers light-curing cement (Heliosit Orthodontic; Ivoclar Vivadent) the mean shear bond strength was 10.38 Mpa. Tukey’s HSD as post-hoc test was used to identify Group 1 had shear bond strength values (15.40 Mpa) significantly higher than Groups 2(6.35 MPa) and 3 (p<0.05). Group 3 had shear bond strength values (10.38 MPa) significantly higher than Group 2 (p<0.05). Comparison of the ARI scores among all the 3 groups showed that ARI scores of 1 which indicated that there was 50% remaining adhesive on porcelain surface and 3 samples with ARI scores of 2 which indicated that more than 50% of remaining adhesive on the porcelain surface. In Group 2, there were 14 samples observed with ARI score of 1 and 2 samples with ARI scores of 2. In Group 3, there were 15 samples observed with ARI scores of 1 and 1 sample with ARI score of 2. No sample occurred with ARI scores of 3 which indicated that 100% of adhesive remained on porcelain surface; and 4 that indicated presence of fractured porcelain surface in all groups.
Conclusion: The conventional orthodontic composite (Transbond™ XT; 3M Unitek) showed the highest shear bond strength as compared to the no-primers adhesives (Orthocern; FGM) and (Heloist Orthodontic; Ivoclar Vivadent). The lowest shear bond strength belonged to the non-primers adhesive (Orthocern; FGM). These findings showed acceptable shear bond strength values among the est groups. The ARI score 1 is the most frequent bond failure in all groups and ARI score 2 is the second mos frequent bond failure occured in the conventional orthodontic composite (Transbond™ XT; 3M Unitek). The non-primer adhesive (Orthocern; FGM) revelead less amount of remaining adhesive on porcelain surface which showed possible decreased risk of porcelain fracture.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Dental materials; Shear bond strength